Autonomous Learning under Study: An Annotated Bibliography from Two Studies with Different Approaches - Doni Marzuki (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2013)
The concept of autonomous  learning  has gained massive attention  in educational  research  and practice  over the last three decades. This concept is regarded as an option in this modern educational  world (Scharle & Szabo, 2000) which demands more active participation and less teacher-  dependence of learners.  In the area  of language  learning,  many researchers have put attention  to this concept in order  to get more understanding of the theory  and  practice.  Two approaches are  commonly used by researchers in this autonomous  learning  matter  are qualitative  and quantitative. These two approaches are discussed in this paper in order to get good comparison  of advantages  and  weaknesses to be used for research  in autonomous  learning  area.  A mix approach or a combination approach between  qualitative   and  quantitative is also  discussed  in  this  paper  to  get  more  ideas  and  understanding about  the alternative way of conducting the research  in this area.